2013
DOI: 10.1007/s00590-013-1216-z
|View full text |Cite
|
Sign up to set email alerts
|

Congenital variations of the upper cervical spine and their importance in preoperative diagnosis. A case report and a review of the literature

Abstract: Several variations of the bony and vascular anatomy around the first and second cervical vertebrae have been reported. Failure to recognise these variations can complicate operations on the upper cervical spine. We present a patient with recent onset of cervical myelopathy due to stenosis at the C3-4 level. Preoperative evaluation identified Klippel-Feil syndrome with cervical fusion of C2-3, aplasia of posterior arch of C1, anomalous vertebral artery course and a "ponticulus posticus" of C2. The combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…These congenital fusions of the cervical vertebrae are consistent with the Klippel-Feil anomaly, Rubinstein-Taybi syndrome and some other disorders [16,21,28,30,40,55].…”
Section: Craniovertebral Anomaliessupporting
confidence: 76%
See 3 more Smart Citations
“…These congenital fusions of the cervical vertebrae are consistent with the Klippel-Feil anomaly, Rubinstein-Taybi syndrome and some other disorders [16,21,28,30,40,55].…”
Section: Craniovertebral Anomaliessupporting
confidence: 76%
“…In some cases, a cleft of another cervical vertebra was seen, as well as a duplication of the cervical vertebral bodies. In other patients, partial or complete fusion affected various cervical vertebrae: C2-C3, C3-C5 or C2-C5 [28,40,45]. In 1 patient thoracolumbo-sacral rachischisis was reported [36].…”
Section: Craniovertebral Anomaliesmentioning
confidence: 99%
See 2 more Smart Citations
“…This bony bridge has been called by different names, but ponticulus posticus is currently the most commonly used term [1][2][3][4][5][6][7][8]. LampropoulouAdamidou et al reported a ''ponticulus posticus'' of axis [9]. Actually, it is not a real ''ponticulus posticus'', because ''ponticulus posticus'' is usually known as an abnormal bony arch of atlas.…”
Section: Introductionmentioning
confidence: 93%